Pengaruh Customer Relationship Management (CRM) terhadap Loyalitas Pelanggan (Studi Kasus Pada Pelanggan Rnd Studio Kota Pariaman) - Sari Rahayu; Nichy Oktaviani; Lili Salfina; Fiqri Rahman (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Companies use CRM to build long-term relationships with customers. The main target of customer relationship management (CRM) is more on customer satisfaction. Customer relationships (CRM) are trust, commitment, communication. The purpose of this study is to determine the effect of trust, commitment and communication simultaneously on the loyalty of RND Studio Cubadak Air Customers in Pariaman City. This type of research is quantitative research. The population in this study were RND Studio customers, sampling was calculated using the Roscoe formula, a sample of 44 respondents. Data collection techniques using questionnaires, while data analysis methods using validity and reliability tests descriptive statistics, classical assumptions, multiple linear regression analysis, and statistical tests. The results of the study indicate that trust has a significant effect on customer loyalty with a value of t count = 3.667> t table = 1.680 at a significant level of 0.001 <0.05, commitment has a significant effect on customer loyalty with a value of t count = 3.622> t table = 1.680 at a significant level of 0.001 <0.05, communication has a significant effect on customer loyalty with a value of t count = 2.617> t table = 1.680 at a significant level of 0.012 <0.05 and trust, commitment and communication simultaneously have a significant effect on customer loyalty with a value of F count = 11.437> F table = 2.70 at a significant level of 0.000 <0.05. The determination coefficient value of 42.1% of customer loyalty can be explained by trust, commitment and communication, while the remaining 57.9% of the customer loyalty value of RND Studio Cubadak Air Kota Pariaman is influenced by other variables not examined in this study.